Microglial activation by microbial neuraminidase through TLR2 and TLR4 receptors. - Fernández-Arjona, María del Mar; Mateos-Grondona, Jesús; Fernández-Llebrez, Pedro; López-Ávalos, María Dolores (Springer Nature, 2019)
Background: Neuraminidase (NA) is a sialidase present, among various locations, in the envelope/membrane of some bacteria/viruses (e.g., influenza virus), and is involved in infectiveness and/or dispersion. The administration of NA within the brain lateral ventricle represents a model of acute sterile inflammation. The relevance of the Toll-like receptors TLR2 and TLR4 (particularly those in microglial cells) in such process was investigated. Methods: Mouse strains deficient in either TLR2 (TLR2-/-) or TLR4 (TLR4-/-) were used. NA was injected in the lateral ventricle, and the inflammatory reaction was studied by immunohistochemistry (IBA1 and IL-1β) and qPCR (cytokine response). Also, microglia was isolated from those strains and in vitro stimulated with NA, or with TLR2/TLR4 agonists as positive controls (P3C and LPS respectively). The relevance of the sialidase activity of NA was investigated by stimulating microglia with heat-inactivated NA, or with native NA in the presence of sialidase inhibitors. Results: In septofimbria and hypothalamus, IBA1-positive and IL-1β-positive cell counts increased after NA injection in wild type (WT) mice. In TLR4-/- mice, such increases were largely abolished, while were only slightly diminished in TLR2-/- mice. Similarly, the NA-induced expression of IL-1β, TNFα, and IL-6 was completely blocked in TLR4-/- mice, and only partially reduced in TLR2-/- mice. In isolated cultured microglia, NA induced a cytokine response (IL-1β, TNFα, and IL-6) in WT microglia, but was unable to do so in TLR4-/- microglia; TLR2 deficiency partially affected the NA-induced microglial response. Conclusions: NA is able to directly activate microglial cells, and it does so mostly acting through the TLR4 receptor, while TLR2 has a secondary role. Accordingly, the inflammatory reaction induced by NA in vivo is partially dependent on TLR2, while TLR4 plays a crucial role. Also, the sialidase activity of NA is critical for microglial activation.
Keywords: Sistema nervioso - Inflamación; Agentes antivíricos; Inflamación (Patología) - Aspectos inmunológicos; Virulencia (Microbiología); Receptores celulares; N-acetyl-2,3-dehydro-2- deoxyneuraminic acid; TLR2; TLR4; Microglia; Neuroinflammation; Oseltamivir